Exploring a social geology approach in eastern Indonesia: What are mining territories?. Issue 1 (March 2021) - Erb, Maribeth; Mucek, Adonara Elizabeth; Robinson, Kathryn
Highlights: Social geology focuses on the social impact of geological objects. Different geological processes result in different accessibility and extraction. Minerals found in East Nusa Tenggara and Sulawesi vary in their mining accessibility. Social geological knowledge will lead to better policy making decisions. Abstract: In this paper we suggest it is essential for development planners to utilize a social geology approach in making decisions on mining concessions. This is especially so in newly decentralizing democracies, such as Indonesia, where political decisions on natural resource extraction are often subject to accusations of corruption. We investigate several sites in different provinces in eastern Indonesia, where social consequences are constrained by geology and technology for mining minerals. On Flores Island, in the East Nusa Tenggara province, manganese is found as volcanic-hosted manganese layers, requiring heavy machinery from large mining companies, while in the same province, on Timor Island, sedimentary-hosted manganese, found in softer soils, can be mined by local communities. Political decentralization, fears of environmental destruction, and concerns over mining concessions resulted in resistance growing in the province, especially where companies mine without much benefit felt by local communities. We compare mining in East Nusa Tenggara province with mining in Sulawesi, long known for nickel and gold, where small-scale gold mining boomed in the past decade. We argue taking a social geology approach is the only way to fully understand mineral resources and to develop effective, efficient, and safe policies for the benefit of local and regional actors.